Preliminary selection of acerola genotypes in Brazil - Cavalcante, Ítalo Herbert Lucena [UNESP]; Beckmann, Márkilla Zunete [UNESP]; Martins, Antonio Baldo Geraldo [UNESP]; Campos, Milton César Costa [UNESP] (CABI Publishing, 2007)
Introduction. Breeding studies for acerola (Malpighia glabra) improvement aim at obtaining plants that produce fruits with uniform chemical and physical attributes, including high levels of vitamin C, which can provision the market with fresh fruit and frozen pulp. High variability in fruit quality is observed in Brazilian acerola crops, especially those propagated by seeds. In this context, the objective of our research was to evaluate the physical and chemical characteristics of Brazilian acerola genotype fruits. Materials and methods. Sixteen acerola genotypes were studied in Jaboticabal, São Paulo State, Brazil. A completely randomized design with sixteen treatments and six replications was adopted. Each treatment was represented by one genotype. Several parameters related to fruit quality, such as width, length, weight, pulp percentage, soluble solids (SS), titratable acidity (TA), [SS / TA] ratio and vitamin C content, were evaluated in fruits of the acerola genotypes. The results were submitted to variance analyses, the Tukey test and cluster analysis. Results and discussion. There was a statistical difference between the acerola genotypes studied. Three of them stood out as natural sources of vitamin C. In spite of fruit size, two acerola genotypes were found to have potential for fresh fruit production. In a general form, genotypes that presented a high [SS / TA] ratio had low vitamin C content. Conclusion. The acerola genotypes studied in Jaboticabal presented high variability, forming eleven groups in relation to fruit quality parameters. © 2007 Cirad/EDP Sciences All rights reserved.
Keywords: Agronomic characters; Ascorbic acid; Brazil; Malpighia glabra; Physicochemical properties; Selection